1987
DOI: 10.1210/endo-120-1-34
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pituitary and Ovarian Changes Occurring during the Anestrus to Estrus Transition in the Golden Hamster*

Abstract: Anestrous hamsters exhibit daily afternoon gonadotropin and progesterone surges, but little estrogen secretion. In the first experiment, short day anestrous females were transferred to long days to detect hormonal changes associated with recovery of cyclicity. Morning and afternoon blood samples were taken at increasing durations in long days. Females autopsied at their first vaginal estrus after transfer to long days differed from long day estrous controls only in their lower uterine weights. Some females at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Concurrent with this anestrous condition, reduced circulating levels of thyroid hormones may also be observed [3,4], This melatonin-induced anestrous condition is similar to that pro duced by short photoperiod [5],…”
mentioning
confidence: 99%
“…Concurrent with this anestrous condition, reduced circulating levels of thyroid hormones may also be observed [3,4], This melatonin-induced anestrous condition is similar to that pro duced by short photoperiod [5],…”
mentioning
confidence: 99%
“…Although the pattern is re miniscent of that seen in anovulatory hamsters induced by short photoperiod, the magnitude of the daily increase in serum LH levels in anovulatory animals would fall between those observed normally for proestrus and non-proestrus [25]. In addition, the animals used in this study exhibited normal signs of cyclicity including a copious vaginal discharge at estrous and a proes trous hormone surge every 4 days.…”
Section: Discussionmentioning
confidence: 58%
“…LHRH and steroid hormones have been shown to regulate pep tide synthesis and glycosylation of hormone peptide subunits [8,26]. Studies of gonadotropin subunit RNAs have revealed that alterations in steady-state levels occur in response to LHRH and the gonadal steroids [25]. Recent reports on LH, FSH, and Prl mRNAs in rats have shown that these transcripts change significantly during the estrous cycle [7,10,11], This is the first report of «, LH|1, Prl, and TSH|5 RNA levels in the female hamster over the 4-day estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In females, adult FR decreased the proportions of individuals exhibiting normal estrous cycles and uterine horn mass regardless of juvenile food availability. The difference in estrous cyclicity was observed in the absence of changes in basal serum LH concentrations, which is not surprising because morning, or basal, LH levels are very low (<1 ng/ml), near the level of assay detectability, and are not different between noncycling and cycling female Syrian hamsters (Jorgenson & Schwartz, 1987). It is important to note that in view of the pulsatile nature of LH secretion, our sampling regimen, three single blood samples in a 6–7 week period, was too infrequent to detect any changes in LH pulse frequency or amplitude that may have occurred during development and adult FR, and that may be physiologically relevant to HPG axis function.…”
Section: Discussionmentioning
confidence: 81%